2020
DOI: 10.1016/s2155-8256(20)30011-9
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perceptions of Joint Commission International Accreditation on Patient Safety in Tertiary Care in South Korea: A Pilot Study

Abstract: Objectives:To explore nurses' attitudes toward Joint Commission International (JCI) accreditation and its perceived impact on patient safety, as well as the perceived degree of implementation of the International Patient Safety Goals (IPSG), in tertiary care in South Korea. Methods: A cross-sectional observational study was conducted consisting of an online questionnaire (N = 76) and a semi-structured Skype interview (N = 5). Sampling focused on nurses working in South Korean tertiary hospitals with an aim to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
1
14
0
2
Order By: Relevance
“…Accreditation and quality enhancements(4,22,23), and thereby, patient satisfaction is correlated positively by many researchers(9,2430). Despotou et al,(31), Carlson-Stevens et al,(32) and Turrioni et al,(22) confirmed the positive impact of accreditation in tertiary care in South Korea, India, and Brazil respectively. Ghareeb, Said & El Zoghbi(33) found a positive impact of accreditation in the primary healthcare settings in Qatar.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Accreditation and quality enhancements(4,22,23), and thereby, patient satisfaction is correlated positively by many researchers(9,2430). Despotou et al,(31), Carlson-Stevens et al,(32) and Turrioni et al,(22) confirmed the positive impact of accreditation in tertiary care in South Korea, India, and Brazil respectively. Ghareeb, Said & El Zoghbi(33) found a positive impact of accreditation in the primary healthcare settings in Qatar.…”
Section: Introductionmentioning
confidence: 91%
“…Accreditation and quality enhancements (4,22,23), and thereby, patient satisfaction is correlated positively by many researchers(9,24-30). Despotou et al, (31), Carlson-Stevens et al, (32) and Turrioni et al, (22) To get an authentic number of samples, 10% of the number of beds from each stratum was included in the study except GHs (15%), where there was only one GH accredited in Kerala (Table 2)…”
Section: Impact Of Accreditation On Quality Enhancement and Patient Smentioning
confidence: 99%
“…Os autores expõem que antes da acreditação havia ambiguidade e falta de clareza na descrição dos procedimentos e nas responsabilidades dos enfermeiros quando ocorriam incidentes. Após a AH esses profissionais sabem como notificar os eventos e possuem indicadores específicos que os auxiliam na identificação das falhas 22 .…”
Section: O Papel Assistencial Do Enfermeiro Na Ahunclassified
“…Nevertheless, nurses also highlighted some drawbacks of this process, such as the high cost and workload increase. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, nurses also highlighted some drawbacks of this process, such as the high cost and workload increase. 7 Other studies explored the perceptions of various providers such as physicians, radiologists, medical technologists, and other allied healthcare professionals. Algahtani et al conducted a cross-sectional to study the perceptions of health professionals towards this process.…”
Section: Introductionmentioning
confidence: 99%